The Effectiveness of Herbal Supplements on Improving the Anthropometric Status of Stunted Children - Hardia, Lukman; Akrom, Akrom; Sulistyani, Nanik (Jurnal Kesehatan Manarang, 2025)
Stunting has become a health issue that threatens the future generation of Indonesia, which is why the government has set a target prevalence of stunting at 14% by 2024. This has become a challenge because some areas, such as Sorong Regency, still have a higher prevalence of stunting compared to the national prevalence. One of the causes of stunting is malnutrition, so efforts are needed to address this issue by utilizing Indonesia's natural wealth, such as herbal honey, Curcuma xanthorrhiza, and black cumin, which are widely used by the community to tackle various health problems. The objective is to determine the effect of administering herbal honey made from temulawak and black cumin on changes in the anthropometric status of stunted children in Sorong Regency. This type of research is quantitative, using a quasi-experimental research design with a pre- and post-test with a control group design. The sampling technique used is purposive sampling, with a total sample of 60 children divided into 3 groups: the normal control group (20 children), the stunting control group (20 children), and the stunting intervention group (20 children). The data analysis techniques used in the research are paired-samples t-test and independent-samples t-test. The statistical test of the mean difference between the pre- and post-test between the intervention group and the control group showed a significant increase in body weight (average increase of 1.60 ± 0.66 kg, p < 0.001), height (1.49 ± 0.74 cm, p < 0.001), and z-score height-for-age (-0.42 ± 0.22 SD, p < 0.001). The administration of herbal honey, Curcuma xanthorrhiza, and black cumin can improve the anthropometric status of stunted children in Sorong Regency.